Meta-Analysis Reveals Transcription Factor Upregulation in Cells of Injured Mouse Sciatic Nerve - Li, Mingchao; Banton, Matthew C.; Min, Qing; Parkinson, David B.; Dun, Xinpeng (Frontiers in Cellular Neuroscience, 2021)
Following peripheral nerve injury, transcription factors upregulated in the distal nerve play essential roles in Schwann cell reprogramming, fibroblast activation and immune cell function to create a permissive distal nerve environment for axonal regrowth. In this report, we first analysed four microarray data sets to identify transcription factors that have at least two-fold upregulation in the mouse distal nerve stump at day 3 and day 7 post-injury. Next, we compared their relative mRNA levels through the analysis of an available bulk mRNA sequencing data set at day 5 post-injury. We then investigated the expression of identified TFs in analysed single-cell RNA sequencing data sets for the distal nerve at day 3 and day 9 post-injury. These analyses identified 55 transcription factors that have at least two-fold upregulation in the distal nerve following mouse sciatic nerve injury. Expression profile for the identified 55 transcription factors in cells of the distal nerve stump was further analysed on the scRNA-seq data. Transcription factor network and functional analysis were performed in Schwann cells. We also validated the expression pattern of Jun, Junb, Runx1, Runx2 and Sox2 in the mouse distal nerve stump by immunostaining. The findings from our study not only could be used to understand the function of key transcription factors in peripheral nerve regeneration but also could be used to facilitate experimental design for future studies to investigate the function of individual TFs in peripheral nerve regeneration.